The multiplicity of modernity or the variety of forms of the modernity? - Scherback, Svitlana (Actual Problems of Mind, 2017)
The theory of multiple modernities insists that modernity presents different answers in different societies depending on the previous path of development, cultural and institutional inheritance. Many social theorists recognize this variety of answers. Those who stress the infrastructural and institutional components of the social development insist on the unity of modern civilization. However, those who study evolution of societies in respect to cultural dynamic prefer to speak of multiple modernities.